Improvements in the Rearing of the Tachinid Parasitoid Exorista larvarum (Diptera: Tachinidae): Influence of Adult Food on Female Longevity and Reproduction Capacity. Issue 2 (7th March 2019) - Dindo, Maria Luisa; Rezaei, Mehran; De Clercq, Patrick
Abstract: Exorista larvarum (L.), a polyphagous gregarious larval parasitoid of lepidopterans, can be mass produced both in vivo, using the greater wax moth Galleria mellonella (L.) (Lepidoptera: Pyralidae) as a factitious host, and in vitro, on artificial media composed of crude components. The present study was focused on another aspect of E. larvarum rearing, namely the influence of adult food on parasitoid performance. The standard food, consisting of lump sucrose and cotton balls soaked in a honey and water solution (1), was compared with other foods or food combinations, namely lump sucrose alone (2), honey and water solution (3), sucrose and water solution either alone (4) or combined with bee-collected pollen (5), and, finally, pollen alone (6). All foods were provided together with distilled water supplied in drinking troughs. Based on the parameters considered (i.e., female longevity, number of eggs laid on host larvae, puparia obtained from eggs, and adults emerged from puparia), pollen alone was deemed to be the most suitable food for adult females of E. larvarum . In particular, the pollen showed a longevity-promoting effect, increasing the number of eggs laid on host larvae throughout the female lifespan. The use of this adult food may also result in a higher flexibility of the management of E. larvarum colonies because it can be replaced weekly, as no desiccation or mold infections were ever found to occur.